Austrian Economics, Evolutionary Psychology and Methodological Dualism: Subjectivism Reconsidered - Viktor J. Vanberg (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2004)
The methodological individualism and subjectivism of the Austrian tradition in economics is often associated with a methodological dualism, i.e. the claim that the nature of its subject matter, namely purposeful and intentional human action, requires economics to adopt a methodology that is fundamentally different from the causal explanatory approach of the natural sciences. This paper critically examines this claim and advocates an alternative, explicitly naturalistic and empiricist outlook at human action, exemplified, in particular, by the research program of evolutionary psychology. It is argued that, within the Austrian tradition, a decidedly naturalistic approach to subjectivism can be found in F.A. Hayek's work.
Keywords: B41; A12; 330; Austrian economics; evolutionary psychology; methodological dualism; subjectivism; Österreichische Schule; Evolutionsökonomik; Sozialpsychologie; Methodologischer Individualismus; Theorie